Keeping nurses in nursing: a qualitative study of German nurses’ perceptions of push and pull factors to leave or stay in the profession - Roth, Catharina; Wensing, Michel; Breckner, Amanda; Mahler, Cornelia; Krug, Katja; Berger, Sarah (BMC nursing, 2022)
The increasing nursing shortages worldwide has focused attention on the need to find more effective ways to recruit and retain nurses. The aim of this study was to gain understanding of factors that keep German nurses in nursing and explore their perceptions of factors that contribute to nurses leaving or staying in the profession.